NILAI RUJUKAN SOLUBLE TRANSFERRIN RECEPTOR (sTfR) {(Soluble Transferrin Receptor Refence Value (sTfR)} - Anggraini Iriani; Endah Purnamasari; Riadi Wirawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Iron in plasma is carried by transferrin delivered to cells through the interaction with a specific membrane receptor, namelytransferrin receptor. The soluble transferrin receptor (sTfR) is a transferrin receptor monomer which lost its first 100 amino acids, andcirculates in the form of transferrin and its receptor complex. Erythroblasts and reticulocytes are the main source of serum TfR Theconcentration of sTfR in serum is useful to diagnose iron deficiency, especially for patient with chronic disease. A new parameter sTfRis reported to be a surrogate marker of bone marrow iron store. The sTfR concentration can describe the functional iron status whileferritin reflects the iron storage status. The aim of this study was to know a reference interval of sTfR in normal adults by provision.Subjects were 157 healthy adults from clinical medical check up who had met the inclusion criteria and were willing to participate asresearch subjects. Soluble Transferrin Receptor (sTfR) examination was performed using reagents from Roche. The statistical calculationswere performed by SPSS 22. The results showed that there was no significant difference between sTfR levels in men and women as wellas in the age group ≤40 years and >40 years. The STfR reference value in this study was calculated based on 95% CI (X±2SD), is0.197–0.598 mg/dL. It can be concluded that the sTfR reference value is 0.197–0.598 mg/dL.